Photography and urban space: Representations of class and women in Erik Prasetya's work - Aji, Daru Tunggul; Mohd Shuib, Ahmad Sofiyuddin bin; Chindany, Amar Leina; Andrea, Novan Jemmi (Jurnal Komunikasi, 2025)
Through photography, the city is not merely a spatial space, but also positioned as a medium. The subjects of the photographs are presented in a political context to depict the reality between humans and the city. This article investigates the relationship between photography and urban space through Erik Prasetya's photographic works, which are divided into two forms. First, the visual representation of workers on the street. Second, the representation of women in relation to the image of modernity. Using Gillian Rose's visual methodology, visual data is analyzed to show the representation of the working class on the one hand, and women on the other. The results of the study indicate a gap between the image of modernity and the working class. The working class in Jakarta struggles to experience modernity fully. Meanwhile, in the second classification, the visual analysis reveals that metropolitan women are portrayed as having freedom in private spaces (malls with all their modernity), even though what is actually represented is the bondage to the pressures of modernity itself.